ANALISIS INSTRUMEN PENILAIAN, PENSKORAN DAN PENENTUAN NILAI - Diah Dwi Sartika; Syifa Munawarah; Mawaddataw Warohmah; Yumna Kamilah Daulay; Fitri (As-Sulthan Journal of Education, 2026)
This study aims to analyze the quality of assessment instruments, focusing on scoring and grade determination in the learning process. Assessment instruments are essential components of educational evaluation as they function to measure the achievement of students’ competencies. This study employed a descriptive qualitative approach, using documentation and literature review as data collection techniques. The analyzed data included assessment instruments, scoring rubrics, and grading procedures used by teachers. The results indicate that the assessment instruments were developed based on learning indicators; however, they did not fully meet the principles of validity and reliability. Weaknesses were found in the clarity of scoring criteria and the consistency of score assignment. In addition, grade determination tended to be administrative and had not been optimally utilized as feedback for learning improvement. Therefore, a systematic analysis of assessment instruments is necessary to enhance objectivity, fairness, and accuracy in assessment results. This study is expected to contribute to improving the quality of educational assessment practices.